Two-dimensional / three-dimensional perovskite thin film material and preparation method and application thereof

CN123035849APending Publication Date: 2026-11-03HUANGSHAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611137044.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

现有研究中,传统氨基配体与甲脒基3D钙钛矿的晶格适配性瓶颈导致2D/3D界面处晶格失配,引发能带偏移和界面复合损失,影响钙钛矿太阳能电池的稳定性和效率。

Method used

Two-dimensional/three-dimensional perovskite films were prepared by a two-step method using pyridine-2,6-bis(formamidinium) dihydrochloride as an additive. The planar conjugated configuration and multiple N-H active sites were utilized to react with PbI2 precursor solution to form high-quality 2D/3D heterostructure perovskite films, thereby regulating crystallization kinetics and passivating defects.

Benefits of technology

The photoelectric conversion efficiency of perovskite solar cells was improved from 21.83% to 24.18%, and the stability of the devices was significantly enhanced. After aging in air for 1000 hours, the devices still retained 93.83% of their initial performance, demonstrating the potential for low-cost and large-scale fabrication.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123035849A_ABST
    Figure CN123035849A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of photovoltaic new energy materials and devices, and particularly relates to a two-dimensional / three-dimensional perovskite film material and a preparation method and application thereof. The application comprises the following steps: a lead iodide precursor solution containing pyridine-2,6-bis(formamidine) dihydrochloride is spin-coated on a substrate, a lead iodide film is formed on the substrate after annealing, two-dimensional perovskite seeds are formed on the lead iodide film, an organic amine salt solution is spin-coated on the center of the lead iodide film, and a two-dimensional / three-dimensional perovskite film is formed after annealing. The perovskite film is prepared by a two-step method, pyridine-2,6-bis(formamidine) dihydrochloride is added into a PbI2 precursor solution by an additive engineering, a lead iodide film is formed, and a high-quality perovskite film with larger preferential orientation crystal domains is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of photovoltaic new energy materials and devices technology, and particularly relates to a two-dimensional / three-dimensional perovskite thin film material, its preparation method and application. Background Technology

[0002] Among numerous new energy sources, solar energy, with its unique advantages, has become a shining star in the energy transition. With its many benefits, solar energy is playing an increasingly important role in the global energy transition.

[0003] Perovskite solar cells, representing third-generation photovoltaic technology, have significantly improved their power conversion efficiency (PCE) from 3.8% in the initial research and development phase in 2009 to over 27%, demonstrating their technological competitiveness in the new energy field. However, the degradation of perovskite solar cells under long-term environmental conditions such as light, heat, oxygen, and humidity remains a major obstacle to their practical application. To address this issue, researchers have proposed various strategies, among which the construction of two-dimensional / three-dimensional (2D / 3D) perovskites is considered a highly promising solution. By integrating 2D perovskites into 3D perovskite structures, grain boundaries and surface defects can be effectively passivated, ion migration can be suppressed, and carrier transport can be improved, thereby enhancing the stability and efficiency of the material.

[0004] Although the chemical diversity of organic ligands (such as amino cations like PEA+ and BA+) in 2D perovskites has been extensively explored, current research remains limited by the lattice compatibility bottleneck between traditional amino ligands and formamidinium-based 3D perovskites (FAPbI3). Specifically, the larger formamidinium cations (~2.8 Å in diameter) in FAPbI3 induce [PbI6]... 4- Octahedral ligands undergo lattice distortion. When co-assembled with linear alkylamino ligands, lattice mismatch occurs at the 2D / 3D interface due to ligand steric hindrance, leading to band shift and interfacial recombination losses. In contrast, amidine ligands, with their planar conjugated configuration and multiple N-H active sites, can interact with [PbI6]. 4- Octahedral structures form a three-center hydrogen bond network, enabling lattice strain release. However, current research on amidine-based 2D perovskites is limited to sporadic reports. Summary of the Invention

[0005] To overcome the shortcomings of the prior art, this invention provides a two-dimensional / three-dimensional perovskite thin film material, its preparation method, and its applications. This invention prepares perovskite thin films via a two-step method. Using additive engineering, pyridine-2,6-bis(formamidinium) dihydrochloride is added to a PbI2 precursor solution to form a lead iodide thin film, resulting in a high-quality perovskite thin film with larger preferred orientation domains.

[0006] To achieve one of the above objectives, the present invention adopts the following technical solution: A method for preparing two-dimensional / three-dimensional perovskite thin film materials includes the following steps: Pyridine-2,6-bis(formamidinium) dihydrochloride (2,6-PyFA2Cl2) was added to a lead iodide (PbI2) precursor solution to obtain a mixed solution. The mixed solution was spin-coated onto a substrate, and after annealing, a lead iodide film was formed on the substrate. Two-dimensional (2D) perovskite seed crystals were formed on the lead iodide film. An organic amine salt solution was then spin-coated onto the center of the lead iodide film, and after annealing, a two-dimensional / three-dimensional (2D / 3D) perovskite film was formed.

[0007] Preferably, the lead iodide precursor solution is prepared by adding lead iodide solution and pyridine-2,6-bis(formamidinium) dihydrochloride in a nitrogen glove box to a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide.

[0008] Preferably, the concentration of the lead iodide solution is 1-2 mol / L, the volume ratio of N,N-dimethylformamide (DMF) to dimethyl sulfoxide (DMSO) is (1-10):1, and the concentration of pyridine-2,6-bis(formamidinium) dihydrochloride in the lead iodide precursor solution is 0.05-1 mol / L.

[0009] Preferably, the amount of lead iodide precursor solution spin-coated onto the substrate is 20–60 μL, the spin-coating speed is 1000–3000 rpm, the duration is 20–60 seconds, the annealing temperature is 50–100°C, and the annealing time is 1–10 minutes.

[0010] Preferably, the solvent for the organic amine salt solution is isopropanol, and the solutes are formamidinium hydroiodate (FAI), methyl ammonium chloride (MACl), and methyl ammonium iodide (MAI), with a mass ratio of (100-300):(1-30):1, and the concentrations of formamidinium hydroiodate, methyl ammonium chloride, and methyl ammonium iodide are 0.523M, 0.133M, and 0.004M, respectively. The organic amine salt solution is obtained by dissolving formamidinium hydroiodate, methyl ammonium chloride, and methyl ammonium iodide in isopropanol in a nitrogen glove box by shaking for 1-10 hours.

[0011] Preferably, the amount of organic amine salt solution used is 20-60 μl, the spin coating speed of the organic amine salt solution is 1000-3000 rpm, the duration is 20-60 seconds, then pre-annealing in air at 20-50°C for 3-10 minutes, and finally annealing in air at 100-200°C for 10-30 minutes, with the ambient humidity during air annealing being 20-40% RH.

[0012] To achieve the second objective mentioned above, the present invention provides a two-dimensional / three-dimensional perovskite thin film material.

[0013] To achieve the third objective mentioned above, this invention provides an application of a method for preparing two-dimensional / three-dimensional perovskite thin film materials, comprising the following steps: S1. Prepare a SnO2 electron transport layer by spin-coating SnO2 solution onto cleaned ITO (indium tin oxide) conductive glass; S2. Prepare a 2D / 3D perovskite light-absorbing layer (i.e., a two-dimensional / three-dimensional perovskite thin film) on the SnO2 electron transport layer according to the preparation method of two-dimensional / three-dimensional perovskite thin film materials. S3. Spin-coating Spiro-OMeTAD (2,2,7,7-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9-spirodifluorene) solution onto a 2D / 3D perovskite light-absorbing layer to prepare a hole transport layer and then oxidizing it in a drying cabinet. S4. A metal back electrode is deposited on the hole transport layer to obtain a 2D / 3D perovskite solar cell.

[0014] Preferably, in step S1, the cleaning steps are as follows: take the etched ITO glass and ultrasonically clean it three times in sequence with conductive glass cleaner, water and anhydrous ethanol, each time for 15 to 20 minutes. After ultrasonic cleaning, blow it dry with nitrogen gas. Then treat it with an ultraviolet ozone cleaner for 15 to 20 minutes.

[0015] Preferably, in step S1, the SnO2 solution is prepared by diluting 15% SnO2 aqueous colloidal dispersion and ice-cold deionized water at a volume ratio of 1:4 and then sonicating in an ice-water bath for 30 minutes. In step S4, a metallic silver electrode is deposited on the hole transport layer using a vacuum thermal evaporation apparatus.

[0016] The advantages of this invention are: (1) This invention prepares high-quality two-dimensional / three-dimensional (2D / 3D) heterostructure perovskite thin films by pre-inserting pyridine-2,6-bis(formamidinium) dihydrochloride (2,6-PyFA2Cl2) as a spacer molecule into the lead iodide framework, thereby improving the carrier transport and extraction rates and the film stability. The photoelectric conversion efficiency of the final perovskite solar cell is increased from 21.83% to 24.18%. More importantly, the modified perovskite solar cell has significantly improved stability, retaining 93.83% of its initial performance after 1000 hours of aging test in air. This preparation method uses simple equipment, has low production cost, and produces high quality.

[0017] (2) This invention prepares perovskite films via a two-step method. Using additive engineering, pyridine-2,6-bis(formamidinium) dihydrochloride (2,6-PyFA2Cl2) is added to the PbI2 precursor solution to form a lead iodide film. This facilitates subsequent cation reactions and promotes the growth of high-quality perovskite films. Furthermore, a 2D perovskite is formed on the lead iodide film, and the crystallization kinetics of the 3D perovskite are adjusted through a template effect, thereby forming a high-quality perovskite film with larger preferred orientation domains. Simultaneously, 2,6-PyFA2Cl2 possesses a planar conjugated configuration and multiple NH active sites, enabling it to react with PbI2. 2+ Lewis acid-base coordination is used to passivate defects in perovskite films, effectively suppressing nonradiative recombination pathways of charge carriers and significantly improving carrier transport characteristics. Most importantly, 2D perovskites exhibit excellent moisture resistance due to the hydrophobicity of the spacer cations, preventing water molecule intrusion and significantly increasing the long-term stability of perovskite films and devices.

[0018] (3) This invention employs a spin-coating method combined with additive-controlled processes, requiring only conventional solution treatment and low-temperature annealing steps, making the process simple and feasible. Furthermore, compared to existing technologies, it features low cost, short production cycle, and can be used for large-scale fabrication of efficient and stable 2D / 3D perovskite solar cells. Attached Figure Description

[0019] Figure 1 The X-ray diffraction patterns are those of the lead iodide films formed during the preparation process of Example 1 and Comparative Example 1.

[0020] Figure 2 The X-ray diffraction patterns are those of the perovskite films formed during the preparation process of Example 1 and Comparative Example 1.

[0021] Figure 3 This is a scanning electron microscope image of the perovskite thin film in Comparative Example 1.

[0022] Figure 4 This is a scanning electron microscope image of the perovskite thin film of Example 1.

[0023] Figure 5 The perovskite solar cells of Example 1 and Comparative Example 1 JV curve.

[0024] Figure 6 The graph shows the long-term stability tracking curves of the perovskite solar cells of Example 1 and Comparative Example 1. Detailed Implementation

[0025] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0026] Example 1

[0027] A 2D / 3D perovskite solar cell includes the following steps: S1. Cleaning ITO conductive glass: Take the etched ITO conductive glass and clean it three times in sequence with conductive glass cleaner, water and anhydrous ethanol, 15 minutes each time. After ultrasonic cleaning, dry it with nitrogen gas and set it aside for use.

[0028] S2. Preparation of SnO2 solution: Dilute 15% SnO2 aqueous colloidal dispersion with ice-cold deionized water at a volume ratio of 1:4 and sonicate in an ice-water bath for 30 minutes.

[0029] S3. Preparation of PbI2 precursor solution: In a nitrogen glove box, add 1.5M PbI2 and 1mL of 2,6-PyFA2Cl2 to 1mL of DMSO / DMF (V DMSO :V DMF PbI2 precursor solution was prepared by shaking and dissolving in a 1:4 mixed solvent.

[0030] S4. Preparation of organic amine salt solution: In a nitrogen glove box, weigh 90 mg FAI, 9 mg MACl and 0.69 mg MAI respectively and dissolve them in 1 mL isopropanol. Shake for 2 h for later use.

[0031] S5. Preparation of Spiro-OMeTAD solution: In a nitrogen glove box, weigh 72.3 mg of Spiro-OMeTAD into a glass reagent bottle, add 1 mL of chlorobenzene, and stir to dissolve to obtain a clear solution. Then, use a pipette to add 17.5 μL of Li-TFSI solution (520 mg of Li-TFSI (lithium bis(trifluoromethanesulfonylimide)) dissolved in 1 mL of acetonitrile) and 28.8 μL of t-BP (4-tert-butylpyridine) to the above clear solution, and stir magnetically for more than 2 h.

[0032] S6. Preparation of the electron transport layer: Before spin coating, the ITO conductive glass cleaned in step S1 was treated with an ultraviolet ozone cleaner for 15 min. 60 µL of SnO2 solution was evenly spread onto the ITO conductive glass. The spin coating process was: 3500 rpm, 30 s (2000 rpm·s). -1 After spin coating, the substrate was transferred to a heating stage and annealed at 150 °C for 30 min to obtain an ITO / SnO2 substrate.

[0033] S7. Preparation of 2D / 3D perovskite films: First, the ITO / SnO2 substrate was treated with a UV ozone cleaner for 20 min and then transferred to a nitrogen-filled glove box. Next, 30 µL of the PbI2 precursor solution prepared in step S3 was uniformly spread onto the ITO / SnO2 substrate using a spin-coating process of 1500 rpm for 30 s (1500 rpm·s). -1 After spin coating, the film was transferred to a flat heating stage and annealed at 70 °C for 1 min. After cooling to room temperature, a lead iodide film was formed (X-ray diffraction pattern as shown). Figure 1 As shown in the figure, 30 µL of organic amine salt was spin-coated onto a lead iodide film (2000 rpm, 25 s), annealed at 30 °C for 5 min, and then transferred to air for annealing at 150 °C for 30 min to form a two-dimensional / three-dimensional perovskite film (X-ray diffraction pattern as shown). Figure 2 (As shown).

[0034] S8. Preparation of the hole transport layer: After the two-dimensional / three-dimensional perovskite film has cooled, 40 µL of Spiro-OMeTAD solution is spread evenly on the surface of the two-dimensional / three-dimensional perovskite film. The spin-coating process is: 3000 rpm, 30 s (2000 rpm·s). -1 After spin coating, transfer to a drying oven for oxidation for 12 hours.

[0035] S9. Fabrication of the metal back electrode: The oxidized device is transferred onto the mask of the evaporation equipment, and vacuum thermal evaporation is performed at a vacuum degree of less than 4 × 10⁻⁶. -4 A complete 2D / 3D perovskite solar cell was fabricated by depositing a 100 nm thick metallic silver electrode on the hole transport layer under the condition of Pa.

[0036] Comparative Example 1

[0037] The difference between this comparative example and Example 1 is that 1 mL of 2,6-PyFA2Cl2 is not added in step S3, while the other steps are the same as in Example 1.

[0038] The performance of the 2D / 3D perovskite solar cell prepared in Example 1 and the lead iodide thin film, perovskite thin film, and perovskite solar cell prepared in Comparative Example 1 were tested. Specifically: I. Phase and Morphology Analysis of Perovskite Thin Films (1) X-ray diffraction tests of lead iodide thin films and perovskite thin films of Comparative Example 1 and Example 1 Figure 1 The images shown are XRD patterns of the lead iodide films formed during the preparation process of Example 1 and Comparative Example 1. Figure 1It can be seen that after the introduction of 2,6-PyFA2Cl2, the intensity of the PbI2 diffraction peak at 2θ = 12.7° gradually decreases, while the corresponding full width at half maximum (FWHM) increases significantly, indicating that the crystallinity and grain size of the PbI2 film are reduced. This suggests that the bulky 2,6-PyFA2Cl2 cations are effectively embedded in the inorganic PbI2 framework, disrupting the stacking of the face-shared layered structure.

[0039] Figure 2 These are the XRD patterns of the perovskite films formed during the preparation process of Example 1 and Comparative Example 1. Figure 2 It can be seen that the perovskite film of Comparative Example 1 exhibits a high PbI2 diffraction peak intensity, indicating that the PbI2 film structure is compact and insufficiently wetted, resulting in incomplete conversion during the reaction with organic amine salts. In contrast, the perovskite film of Example 1 shows a significantly reduced PbI2 diffraction peak intensity and a further increase in perovskite crystallinity, indicating that the introduction of 2,6-PyFA2Cl2 promotes the conversion of PbI2 to the perovskite phase. A high-quality perovskite film facilitates carrier transport, providing a crucial structural foundation for improved device performance. Furthermore, the perovskite film of Example 1 shows a new diffraction peak at 2θ = 8.2°. According to the Bragg equation, diffraction peaks within a small angle range can be attributed to the formation of a low-dimensional phase after the introduction of a larger cation. This indicates the formation of a 2D perovskite, which can effectively passivate defects at the perovskite-hole transport layer interface, thereby improving device performance. Simultaneously, its hydrophobic properties contribute to outstanding long-term stability.

[0040] (2) Scanning electron microscopy test of the perovskite thin films formed during the preparation process of Example 1 and Comparative Example 1

[0041] Figure 3 The image shown is a top-view scanning electron microscope image of the perovskite thin film in Comparative Example 1. Figure 3 It is known that the original perovskite exhibits a small particle structure with a large number of residual PbI2 nanosheets on the surface. These structural defects, acting as nonradiative recombination centers, exacerbate the nonradiative recombination process of charge carriers, thereby leading to increased energy loss and reduced photoelectric performance of the device.

[0042] Figure 4 This is a top-view scanning electron microscope image of the perovskite film of Example 1. In contrast, the modified perovskite film exhibits a significantly increased grain size and a more uniform surface. This improvement is attributed to the interaction between 2,6-PyFA2Cl2 and PbI2, which modulates the nucleation process and improves the crystallinity of the perovskite film, resulting in a higher quality perovskite layer and thus enhancing the photoelectric performance and stability of the battery.

[0043] II. Photoelectric Performance and Stability Analysis of Perovskite Solar Cells

[0044] (1) The perovskite solar cells prepared in Example 1 and Comparative Example 1 JV Curve test

[0045] Figure 5 For standard AM 1.5G (100 mW·cm) -2 The perovskite solar cells prepared in Example 1 and Comparative Example 1 under illumination conditions JV The curve test graph shows that the perovskite solar cell of Example 1 has superior photoelectric performance. Detailed photovoltaic parameters are summarized in Table 1 below: Table 1

[0046] Analysis of the data in Table 1 shows that the power conversion efficiency (PCE) of the perovskite solar cell in Comparative Example 1 is 21.83%, and the open-circuit voltage is ( V OC The voltage is 1.09 V, the fill factor is 81.60%, and the current density is ( J SC The value is 24.54 mA·cm. -2 In contrast, the perovskite solar cell of Example 1... V OC The voltage was significantly increased to 1.15 V, the FF was improved to 84.00%, and the best PCE reached 24.18%, which was significantly higher than the perovskite device in Comparative Example 1.

[0047] (2) Long-term stability tracking of perovskite solar cells prepared in Example 1 and Comparative Example 1

[0048] Figure 6 This is a long-term stability tracking curve of the perovskite solar cells prepared in Example 1 and Comparative Example 1 in an air environment (relative humidity 40±10%). The curve shows that the PCE of the device prepared in Comparative Example 1 only maintained 75.06% of its initial efficiency after 1000 h of tracking, while the stability of the device based on Example 1 was significantly improved, maintaining 93.83% of its initial efficiency after 50 days. This indicates that the introduction of 2,6-PyFA2Cl2 effectively blocked the effects of light and water / oxygen, inhibited the degradation of perovskite, and significantly improved the long-term stability of the device.

[0049] The above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing two-dimensional / three-dimensional perovskite thin film materials, characterized in that, Includes the following steps: A lead iodide precursor solution containing pyridine-2,6-bis(formamidinium) dihydrochloride was spin-coated onto a substrate. After annealing, a lead iodide film was formed on the substrate, and two-dimensional perovskite seed crystals were formed on the lead iodide film. An organic amine salt solution was then spin-coated onto the center of the lead iodide film, and after annealing, a two-dimensional / three-dimensional perovskite film was formed.

2. The method for preparing a two-dimensional / three-dimensional perovskite thin film material according to claim 1, characterized in that, The lead iodide precursor solution was prepared by adding lead iodide solution and pyridine-2,6-bis(formamidinium) dihydrochloride in a nitrogen glove box to a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide.

3. The method for preparing a two-dimensional / three-dimensional perovskite thin film material according to claim 2, characterized in that: The concentration of the lead iodide solution is 1-2 mol / L, the volume ratio of N,N-dimethylformamide to dimethyl sulfoxide is (1-10):1, and the concentration of pyridine-2,6-bis(formamidinium) dihydrochloride in the lead iodide precursor solution is 0.05-1 mol / L.

4. The method for preparing a two-dimensional / three-dimensional perovskite thin film material according to claim 1, characterized in that: The amount of lead iodide precursor solution spin-coated onto the substrate is 20–60 μL. The spin-coating speed of the lead iodide precursor solution is 1000–3000 rpm, the duration is 20–60 seconds, the annealing temperature is 50–100℃, and the annealing time is 1–10 minutes.

5. The method for preparing a two-dimensional / three-dimensional perovskite thin film material according to claim 1, characterized in that: The solvent for the organic amine salt solution is isopropanol, and the solutes are formamidinium hydroiodate, methylammonium chloride, and methylammonium iodide, with the concentrations of formamidinium hydroiodate being 0.523M, methylammonium chloride being 0.133M, and methylammonium iodide being 0.004M. The organic amine salt solution is obtained by dissolving formamidinium hydroiodate, methylammonium chloride, and methylammonium iodide in isopropanol in a nitrogen glove box by shaking for 1–10 hours.

6. The method for preparing a two-dimensional / three-dimensional perovskite thin film material according to claim 1, characterized in that: The amount of the organic amine salt solution used is 20-60 μl, the spin coating speed of the organic amine salt solution is 1000-3000 rpm, the duration is 20-60 seconds, then it is pre-annealed in air at 20-50°C for 3-10 minutes, and finally annealed in air at 100-200°C for 10-30 minutes, with the ambient humidity during air annealing being 20-40% RH.

7. A two-dimensional / three-dimensional perovskite thin film material prepared by the preparation method according to any one of claims 1-6.

8. The application of a method for preparing two-dimensional / three-dimensional perovskite thin film materials as described in any one of claims 1-6, characterized in that, Includes the following steps: S1. Prepare a SnO2 electron transport layer by spin-coating SnO2 solution onto cleaned ITO conductive glass; S2. Prepare a 2D / 3D perovskite light-absorbing layer on the SnO2 electron transport layer according to the preparation method of two-dimensional / three-dimensional perovskite thin film materials; S3. Spin-coating Spiro-OMeTAD solution onto a 2D / 3D perovskite light-absorbing layer to prepare a hole transport layer and then oxidizing it in a drying cabinet; S4. A metal back electrode is deposited on the hole transport layer to obtain a 2D / 3D perovskite solar cell.

9. The application of the method for preparing two-dimensional / three-dimensional perovskite thin film materials according to claim 8, characterized in that, In step S1, the cleaning steps are as follows: Take the etched ITO glass and ultrasonically clean it three times in sequence with conductive glass cleaner, water and anhydrous ethanol, each time for 15 to 20 minutes. After ultrasonic cleaning, blow it dry with nitrogen gas. Then treat it with ultraviolet ozone cleaning machine for 15 to 20 minutes.

10. The application of the method for preparing a two-dimensional / three-dimensional perovskite thin film material according to claim 8, characterized in that: In step S1, the SnO2 solution is prepared by diluting 15% SnO2 aqueous colloidal dispersion and deionized water at a volume ratio of 1:4 and then sonicating in an ice-water bath for 30 minutes. In step S4, a metallic silver electrode is deposited on the hole transport layer using a vacuum thermal evaporation apparatus.